Análises ecológicas de duas espécies de felídeos (Leopardus geoffroyi e L. colocolo) em áreas antropizadas da Savana Uruguaia - Tirelli, Flávia Pereira (2017)
The Geoffroy‘s cat (Leopardus geoffroyi) and the pampas cat (L. colocolo) are small Neotropical felids that typically occur in open landscapes. These species are distributed simpatricaly in the Uruguayan Savannah ecoregion. In this region, Geoffroy‘s cat and pampas cat are considered, respectively, to be abundant and rare species. The present study aimed to evaluate these propositions and to characterize ecological aspects of these species in this threatened ecoregion. The study was conducted from November 2013 to September 2015 in privately owned areas in ―Serra do Caverá‖, southernmost Brazil. We installed and monitored 26 camera-traps and we performed eight capture campaigns aiming to fit individuals of both species with VHF radio-collars and to collect blood samples. As a result, we obtained 516 image records of Geoffroy‘s cat and captured 12 different individuals of same species, seven of which were monitored by radio-telemetry. We did not find any record of pampas cat, which demonstrated the rareness or absence of the species in the study area. From the Geoffroy‘s cat data, we observed that males had home-range (HR), core-area and body weight that were larger than those of females. We also observed that male body weight significantly and positively influenced HR size, whereas in females such relationship was not significant. We observed extensive HR and core area overlap, with minor changes in overlap between seasonal partitions. These results indicate some degree of sociability in this population. Interestingly, our kinship analyses indicated that the majority of the cats sampled in this population were unrelated, and that genetic relatedness did not significantly influence the levels of HR and core area overlap. This indicated that the population, in the studied scale, has a socio-spatial structure that departs from what could be expected based on a model assuming male dispersal and female philopatry. Additionally to the socio-spatial patterns, we also investigated factors that influence the persistence of the species in the threatened Uruguayan Savannah. We observed that this population significantly selected riparian vegetation and avoided open grassland with cattle. It is noteworthy that the protection of riparian vegetation is required by Brazilian national law. Hence, this habitat may provide shelter for Geoffroy‘s cats, and hypothetically it could serve as an ecological corridor for the species, an important issue that should be tested deepened in the future. This population also presented significantly nocturnal activity patterns, which consequently avoids human contact. The density estimation was considered reasonable in comparison to other areas within the Geoffroy‘s cat range, agreeing with the initial estimate for the species in the region. In these studies, we obtained insights that help us understand some ecological characteristics of the species, and to assess the bases for its persistence in these human-dominated landscapes. Such insights could not be obtained for the pampas cat, as it seems to be currently absent from the study site. Its absence or rarity at this site and several others within the ecoregion is a worrisome observation, from a conservation perspective. This is especially the case given that the Uruguayan Savannah contains a distinct ‗Evolutionarily Significant Unit‘ (ESU) of pampas cats. Therefore, in the fourth chapter, we aimed to assess the current spatial distribution and conservation status of the pampas cat in the Uruguayan Savannah. We collected 107 spatial records and constructed two models (with and without anthropogenic variables), each of them built separately with two different algorithms (Maxent and Maxlike). All models were very similar, indicating higher suitability (or probability of occurrence [PO]) in grassland areas from sea level to 400m of altitude. The best-fit models were those including anthropogenic variables, which also yielded a more restricted distribution of higher suitability and higher PO areas, supporting the conclusion that this pampas cat population is affected by human disturbance. The estimation of the population size for high-suitability and high-PO areas resulted in assignment to the ―Critically Endangered‖ and ―Endangered‖ categories, respectively. Based on these results, we highlight the urgent need for conservation plans targeting pampas cats in the Uruguayan Savannah. In the global study, we observed that similar felid species seem to respond differently to human impacts, and obtained results that can contribute to the design of conservation actions aiming to ensure the long-term survival of these two species in this threatened ecoregion.